A model for selecting green suppliers through interval-valued intuitionistic fuzzy multi criteria decision making models. Issue 1 (2nd January 2022) - Mohammadi, Seyedeh Saeedeh; Azar, Adel; Ghatari, Ali Rajabzadeh; Alimohammadlou, Moslem
Abstract : This study sought to construct a model for selecting green suppliers. The study was conducted in three phases: in phase 1, the literature was reviewed based on the meta-synthesis method and experts' opinions were analyzed to create a model composed of 11 dimensions and 40 criteria for selecting green suppliers. In phase 2, intuitionistic fuzzy best-worst method was used to weight the dimensions and criteria. The most important dimension was "green image" and the most important criteria were the "environmental protection system" and a good "public image." In phase 3, four suppliers in the field of medical equipment were assessed and ranked. The study proposed a framework for selecting green supplier selection (GSC) and could prove to be more comprehensive than the existing models as it drew on the meta-synthesis method. Another innovation of the study was its reliance on the intuitionistic fuzzy set theory to overcome ambiguities in selecting suppliers.